2016
DOI: 10.1371/journal.pone.0153646
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Primary Intraosseous Squamous Cell Carcinoma (PIOSCC): A Retrospective Review

Abstract: ObjectivesTo delineate clinical and pathological features and determine the prognostic factors of primary intraosseous squamous cell carcinoma (PIOSCC).Materials and methodsPatients diagnosed with PIOSCC, attending the department of oral and maxillofacial surgery, Nanjing stomatological hospital between 2005 and 2015, were identified and retrospectively reviewed for clinical and pathological characteristics. Therapeutic modalities were measured and related follow-up data recorded, in order to determine prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
42
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 21 publications
6
42
2
Order By: Relevance
“…According to the protocol of treatment guidelines for oral cancers, chemotherapy would be recommended for patients with loco-regionally advanced diseases especially if aggressive features were found, such as positive surgical margins and extracapsular spread in lymph node metastasis 7 . Currently, cisplatin-based chemotherapeutic regimens have been the most widely and frequently used adjuvant treatments against OSCC 8 ; however, chemotherapeutic drugs do not specifically target tumour cells, and thus may have deleterious effects on normal cells. In addition to this, chemotherapy resistance tends to develop as the treatment continues, which is the main cause of tumour relapse and treatment failure 9 .…”
mentioning
confidence: 99%
“…According to the protocol of treatment guidelines for oral cancers, chemotherapy would be recommended for patients with loco-regionally advanced diseases especially if aggressive features were found, such as positive surgical margins and extracapsular spread in lymph node metastasis 7 . Currently, cisplatin-based chemotherapeutic regimens have been the most widely and frequently used adjuvant treatments against OSCC 8 ; however, chemotherapeutic drugs do not specifically target tumour cells, and thus may have deleterious effects on normal cells. In addition to this, chemotherapy resistance tends to develop as the treatment continues, which is the main cause of tumour relapse and treatment failure 9 .…”
mentioning
confidence: 99%
“…Similarly, Wenguang et al retrospectively reviewed all types of PIOC in their 2015 study and found 2-and 5-year survival rates of 68.9% and 38.8% respectively 13 . Furthermore, by univariant and multivariant analysis, they determined adverse prognostic factors to include: advance nodal classification, high histologic grade and positive nodal status 13 . In the cases reviewed here, the patients were disease free at variable follow-up periods, but long-term follow-up is not known.…”
Section: Discussionmentioning
confidence: 97%
“…PIOC has a predilection for males, with a male: female ratio of 2:1, which may be attributed to the higher incidence of odontogenic cysts in males 1,2 . Differential diagnoses for PIOC include, but are not limited to: maxillary sinus neoplasm, alveolar mucosal or gingival carcinoma that has invaded bone, odontogenic tumour or metastasis from a primary tumour elsewhere 13,14 . Elimination of these conditions often delays diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological findings were consistent with oral SCC in cats [ 17 ] and SCC [ 18 ] and solid type PIOSCC in humans [ 6 ]. Given the clinicopathological features in this cat, and since prominent features including cellular atypia, moderate mitotic activity and no true keratinization were observed in the sections examined; this tumor was further classified as a poorly differentiated nonkeratinizing solid type PIOSCC [ 13 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%